Precision Medicine in Heritable Thoracic Aortic Disease (Htad): From Molecular Mechanisms to Genotype-Driven Risk Stratification and Timing of Intervention - Than Xuan Le; Quy Phu Hoang; Dung Duc Doan; Dong Xuan Pham; Thanh Xuan Nguyen (Cardiogenetics, 2026)
Background: Heritable thoracic aortic disease (HTAD) accounts for approximately 20–25% of thoracic aortic aneurysm and dissection (TAAD) cases and is a major cause of premature death in young adults. Methods: This is a narrative, non-systematic review. We performed a selective synthesis of clinical practice guidelines (ACC/AHA 2022, EACTS/STS 2024), the revised Ghent nosology, large multicenter cohort studies (Montalcino Aortic Consortium), randomized pharmacotherapy trials, and molecular mechanism data published between 2010 and 2025; quantitative figures are reported as published in individual primary sources and were not pooled or re-analyzed. Results: The advent of next-generation sequencing (NGS) has driven a paradigm shift in HTAD management, from risk assessment based purely on phenotype (aortic diameter) to risk stratification based on genotype (molecular mutation). The 2022 ACC/AHA guideline identifies eleven genes with confirmed high-penetrance risk for HTAD; these, together with the established Loeys–Dietz gene TGFB3 (recognized through gene–disease validity assessment rather than the ACC/AHA list), can be grouped into three pathogenic mechanisms: extracellular matrix dysregulation, TGF-β signaling dysregulation, and vascular smooth muscle contractile dysfunction. Gene–disease association should be distinguished from guideline-defined classification and regarded as evolving, since additional candidate genes such as LTBP3 are already emerging in gene-negative families. Multigene panel testing identifies a pathogenic or likely pathogenic variant in roughly 8% of patients referred for suspected HTAD, a yield that rises substantially when applied to syndromic or strongly familial presentations. Prophylactic surgical thresholds are individualized by gene and are generally lower (around 4.0 cm) for high-risk TGFBR1/TGFBR2 and PRKG1 variants and higher (around 5.0 cm) for FBN1 and TGFB3, in contrast with the uniform 5.5 cm threshold historically applied to all patients. Randomized trials over the past decade—including the AIMS irbesartan trial, the Marfan Treatment Trialists’ individual patient data meta-analysis, and the celiprolol and irbesartan trials in vascular Ehlers–Danlos syndrome—now provide direct evidence that angiotensin receptor blockade slows the rate of aortic root dilation in Marfan syndrome, with more limited evidence in vascular Ehlers–Danlos syndrome and uncertain effects on dissection or mortality, while valve-sparing aortic root replacement provides durable long-term outcomes in reported single-center experience. These thresholds and pharmacotherapy recommendations rest predominantly on observational cohort, registry, and randomized trial data of varying maturity and should be interpreted as graded, evolving recommendations rather than fixed cut-points. Conclusions: This review synthesizes the molecular pathogenesis, diagnostic nosology, gene-specific epidemiologic and prognostic data, genetic testing yield, pharmacotherapy evidence, surgical outcomes, and updated prophylactic intervention algorithms per the ACC/AHA (2022) and EACTS/STS (2024) guidelines, providing a practical reference framework for individualizing surveillance and surgical decision-making in patients with HTAD.